Wetting behavior of SnO-ZnO-P₂O₅-SiO₂ glass on 60 vol% SiCₚ/Al composites and characterization of the interfacial phases - Guo, Wei (2022)
The phosphate glass having a chemical composition of 49SnO-19ZnO-32P2O5-3SiO2 (mol.%) was prepared in the present work. Then, the wettability of the glass on 60 vol/% SiCp/Al composites was investigated at 550 °C for 20 min. The results verified potential brazibility of high volume SiCp/Al composites with glass. Average contact angle of 26.3° was reached, performing good wettability of the glass on the surface of 60 vol% SiCp/Al composites. The interfacial products were characterized in detail, and the results showed the ZnPO4 layer was formed adjacent to the composites due to the crystallization in the glass braze.